A review of miRNAs accuracy as a diagnostic biomarker in COPD patients - Rexel Kuatama; Louis Fabio Jonathan Jusni; Christa Karina (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is the third highest leading cause of early death amongst other non-communicable diseases characterized by irreversible limitations of airflow. Current reliable classification relies on forced expiratory volume in the first second (FEV1) and forced vital capacity (FVC) measured on spirometry. In order to provide more effective and individualized management, new markers are needed. Accumulating studies has shown the role of miRNA in the pathogenesis of COPD and the progression of the disease. This review aims to provide overview of the diagnostic capabilities of miRNA and identify gaps of knowledge for further studies. Methods: A review based on Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) was conducted with the database from Pubmed, Science Direct, and Proquest using the key word (